Lecture by Dr Stephen Pax Leonard for the World Oral Literature Project Occasional Lecture Series - Leonard, Stephen Pax (2012)
PDF poster, PDF of powerpoint presentation, mp3 of audio Dr Stephen Pax Leonard is a research fellow at Trinity Hall, Cambridge, and research associate at the Scott Polar Research Institute. He has carried out both linguistic and ethnographic fieldwork in Iceland and the Faroe Islands and has become particularly interested in aspects of dialect formation, the role of identity in small language communities as well as language revitalisation and more generally endangered languages and cultures in the Arctic and elsewhere. He has recently started a new project, documenting and researching the endangered oral traditions, verbal behaviour and communicative practices of the Inughuit people in north-west Greenland. World Oral Literature Project